Magnetic Induction Tomography Using Multi-Channel Phase-Domain Transceiver for Structural Health Monitoring - Jeon, Jiyun; Park, Chan Sam; Lee, Sangheon; Chae, Hee Young; Kim, Jae Joon; Son, Hungsun (Institute of Electrical and Electronics Engineers, 2022)
This article aims to develop a miniaturized magnetic induction tomography (MIT) system with a multi-channel phase-domain transceiver integrated circuit (IC). MIT is an imaging technique using phase shift between a primary magnetic field and induced field caused by the conductivity of a target object. Due to the weak strength of time-varying magnetic field, it is difficult to differentiate the magnetic field interaction. In particular, if the conductivity of the target object is low, the induced field is too small to identify the phase difference. The magnetic dipole model is applied to modeling the MIT system and analyzing performance. The model offers an effective means to analyze and visualize magnetic field interaction in multi-channel by the sum of magnetic dipoles. Then, a multi-channel MIT detection device is developed to include the phase-domain transceiver for automatic high-resolution phase measurement and wireless connectivity, achieving enhanced power efficiency and miniaturization. Finally, the multi-channel MIT system is applied to identify the various sizes of cracks on carbon fiber rods. The sensitivity of the system is analyzed by imaging the cracks by multi-channel measurement. The results show that the multi-channel MIT system can be successfully miniaturized and perform the nondestructive test (NDT).